Performance characteristics of shell and tube heat exchanger using sectoral baffle - Jacob Kolawole Adebayo; Ademola Adebukola Dare; Moses Omolayo Petinrin (Journal of Engineering and Applied Science)
Abstract Shell and tube heat exchangers (STHX) play a vital role in a wide range of industrial processes and daily applications. The finite element method was used to solve continuity, momentum, energy, and k-ε turbulent equations that govern STHX. The simulation procedure (SP) was applied to STHX with a single segmental baffle (SB) and 90º, 120º, and 150º sectoral baffles (STB). The baffles were arranged along the tube at 0º, 60º, 120º, 180º, 240º, and 300º orientations. The SP was run at 323.15 and 278.15 K inlet temperatures for shell and tube, respectively, using water as shell-side fluid at a flow rate ranging from 0.5 to 2.50 kg/s. Velocities, temperatures, and pressure obtained from SP were used to evaluate the Relative Performance Index of all the STBs against SB as control. The numerical values of heat transfer coefficient (HTC) and pressure drops (PD) over the shell side along the length of STHX were compared with those obtained from Kern’s method, HTC of STBs was enhanced by 45%, 50%, 55%, 50%, 61%, and 50% with PD of 40%, 25%, 11%, 22%, − 21%, and 22% and performance evaluation coefficient (Q/ΔP) of 63%, 60%, 56%, 59%, 47%, and 59% with field synergy number of 41%, 47%, 53%, 46%, 59%, and 46% for STB90°, RSTB90°, STB120°, RSTB120°, STB150°, and RSTB150° respectively. From the analysis, it was evident that both the 90º and 120º sectoral baffles outperformed the SB, with the 90º sectoral baffle emerging as the most efficient configuration among all those evaluated. This study underscores the importance of baffle design in optimizing heat transfer performance in shell and tube heat exchangers.